The Selectivity and Suitability of Online Learning Resources as Predictor of the Effects of Self-Efficacy on Teacher Satisfaction During the COVID-19 Lockdown - Zhu, Yonghai; Xu, Yingying; Wang, Xinyu; Yan, Shiyu; Zhao, Li (Frontiers in Psychology, 2022)
Online learning resources (OLR) play an important role in teaching and learning in the process of online learning. Teachers will be satisfied with selectable and suitable OLR, which can promote their self-efficacy to facilitate online teaching and learning. This study proposed a model to examine the effects of the selectivity of online learning resources (SE-OLR) and the suitability of online learning resources (SU-OLR) on teachers’ online teaching satisfaction, and the mediating role of technology self-efficacy (TECHN-SE) and online teaching self-efficacy (OT-SE) between them. The results indicated that SE-OLR and SU-OLR positively affected teachers’ online teaching satisfaction; TECHN-SE and OT-SE positively influenced teachers’ online teaching satisfaction, while TECHN-SE and OT-SE played mediating roles between SE-OLR and SU-OLR and teachers’ online teaching satisfaction. The findings have implications for the design and development of OLR to improve teachers’ satisfaction and facilitate students’ learning effectiveness and teachers’ online teaching.